2018
DOI: 10.1021/acs.orglett.8b02353
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Optically Active α-Trifluoromethylamines by Rearrangement of β-Amino-α-trifluoromethyl Alcohols

Abstract: The synthesis of various optically active α-trifluoromethylamines has been realized from β-amino-α-trifluoromethyl alcohols via an aziridinium ion intermediate under kinetic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 58 publications
(18 reference statements)
0
11
0
1
Order By: Relevance
“…The opening of the resulting aziridinium ion 15 is favored on nontrifluoromethylated carbon. [22] In this case the rearranged products can also be obtained with very good yields. The synthesized β-amino-αtrifluoromethyl alcohols 16 can be used as valuable building Scheme 1.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The opening of the resulting aziridinium ion 15 is favored on nontrifluoromethylated carbon. [22] In this case the rearranged products can also be obtained with very good yields. The synthesized β-amino-αtrifluoromethyl alcohols 16 can be used as valuable building Scheme 1.…”
Section: Introductionmentioning
confidence: 90%
“…The authors have presented usability of 16 in the syntheses of dipeptide analogues. [22] Fluorinated aminophosphonates and aminophosphonic acids belong to a group of interesting compounds from the perspective of broad medical applications. [23] Starting from αhydroxy-β-aminophosphonates 17, Kaźmierczak et al showed that depending on the fluorinating reagent used, regioselective control of the opening of resulting aziridinium ion 18 is possible (Scheme 5).…”
Section: Introductionmentioning
confidence: 99%
“…A similar reaction with the fluoride nucleophile yielded a fluorinated product after the formation of an aziridinium ion driven by DAST [58]. The synthesis of various optically active α-trifluoromethyl amines (33) was realized from β-amino-α-trifluoromethylalcohols (31) via an aziridinium ion intermediate (32) under a kinetic condition (Scheme 10) [59].…”
Section: Aziridinium Ions Upon Expulsion Of the Leaving Groupmentioning
confidence: 99%
“…Other halides and pseudohalides were utilized in the second reaction step and the corresponding products (79-83) were isolated in 71-83% yield range. Interestingly, the 1,1,1,3-tetrafluoropropyl moiety previously had limited options in the literature for its preparation 50,72 . Therefore, N-allyl-PMB-amine and N-pyrid-2-ylpiperazine were utilized to demonstrate the feasibility of conditions II in the synthesis of various tetrafluoropropylamines (84, 85).…”
Section: Fluorinated Alkene Synthon With Suitable Leaving Groupmentioning
confidence: 99%
“…1e) [41][42][43][44] . In this respect, the syntheses of homo-and heterofunctionalized, α-trifluoromethyl vicinal diamines [45][46][47][48][49][50][51][52] and other substituted trifluoropropylamines [52][53][54][55] are demanding.…”
mentioning
confidence: 99%